Comparison of WhatsApp and Google Classroom Group Online Learning Models to Student Learning Outcomes - Eka Susilowati (Urogram Studi Pendidikan Matematika, Universitas IVET, 2021)
The purpose of this study was to compare whether there were differences in the learning outcomes of students in the Mathematics Education Study Program of the University of PGRI Adi Buana University Surabaya in the even semester of the 2019/2020 academic year in Calculus I when applying the online learning model using the WhatsApp group and using Google Class and to know which online learning model is better between the two. The research methods used in analyzing this research are using a quantitative research approach. The type of research used is a quasi-experimental research design, namely a posttest only comparison group design. The sampling technique was applied. is a simple random sampling technique where the population is 90 students and the sample used is 45 students from classes 2019 A and 2019 C. The data used in this study are sourced from primary data, namely the scores of the 2019A class and class students' Middle Semester Examination. 2019C and secondary data derived from observations and archives. The data analysis technique used was descriptive data analysis and inferential statistical analysis through a t-test using the MS Excel program. Based on the results of the research and discussion, it can be concluded that the online learning model using WhatsApp Groups is slightly better than using Google Classroom by paying attention to the system that is applied during learning. Keywords: covid 19, WhatsApp group, Google Classroom, daring learning model, comparison.